2019
DOI: 10.1111/apha.13244
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal free‐choice of a high‐calorie low‐protein diet affects leptin signaling through IRS1 and AMPK dephosphorylation in the hypothalami of female rat offspring in adulthood

Abstract: Aim We aimed to investigate whether a dysregulated maternal diet during gestation and lactation induces long‐lasting changes in the hypothalamic control of feeding behavior in the offspring and whether this effect is sex specific. Methods The study included an analysis of appetite‐regulating metabolic hormones and hypothalamic signaling in male and female offspring in adulthood after exposure to a free‐choice high‐calorie palatable low‐protein (P) diet or standard chow (C) during (pre)gestation/lactation (mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 85 publications
(156 reference statements)
0
8
0
Order By: Relevance
“…Traditionally, maternal nutrition studies have focused on offspring metabolic diseases, such as glucose tolerance, insulin resistance, dyslipidaemia, hypertension and obesity, in humans and rodents [ 4 , 30 , 31 ]. However, it is known that continued stress, such as malnutrition with an excess or deficiency in most nutrients, impacting fetal neurodevelopment, can cause neuropsychiatric disorders, including depression, anxiety and attention-deficit/hyperactivity disorder in offspring, even though to adulthood [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, maternal nutrition studies have focused on offspring metabolic diseases, such as glucose tolerance, insulin resistance, dyslipidaemia, hypertension and obesity, in humans and rodents [ 4 , 30 , 31 ]. However, it is known that continued stress, such as malnutrition with an excess or deficiency in most nutrients, impacting fetal neurodevelopment, can cause neuropsychiatric disorders, including depression, anxiety and attention-deficit/hyperactivity disorder in offspring, even though to adulthood [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal nutrition plays a crucial role in the offspring’s brain development during pregnancy and during a critical period after birth. Initial studies on perinatal programming have shown that malnutrition during pregnancy and/or lactation induces metabolic disorders such as hyperphagia, adiposity, hyperlipidemia and glucose intolerance in offspring, even into adulthood [ 1 , 2 , 3 , 4 ]. Moreover, growing evidence has revealed a modulation of the offspring behavior related to depression, anxiety-like behaviors and addiction (preference of hypercaloric foods and drugs) due to the consumption of a hypercaloric diet in the perinatal period, being associated with long-term structural and functional alterations in the neurodevelopment of the prefrontal cortex (PFC) [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…We performed real-time PCR (TaqMan, ThermoFisher Scientific, Waltham, MA, USA) as described previously [107] using specific sets of primer probes from TaqMan ® Gene Expression Assays, as shown in Table S1. Total RNA was extracted from tibia samples using the Trizol ® method according to the manufacturer's instructions (ThermoFisher Scientific).…”
Section: Rna Isolation and Rt-qpcr Analysismentioning
confidence: 99%
“…The alterations induced by nutritional programming in the hypothalamus of offspring are of special relevance given the important role of this brain region in energy homeostasis, appetite and body composition. Maternal malnutrition during the pre/gestational period can affect many hypothalamic signaling systems controlling appetite and energy expenditure [8][9][10]. One of them is the endocannabinoid system, which is involved in numerous functions both in development and adult life, highlighting energy metabolism, feeding behavior, emotional control and neurodegenerative diseases [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%